Vascular stiffness, 24-hour blood pressure profile in patients with hypertension and anxiety-depressive disorders in andro- and menopausal periods - O. V. Timofeeva; V. V. Skibitsky; A. V. Fendrikova; A. V. Skibitsky (Российский кардиологический журнал)
Aim. Identification and analysis of the features of vascular stiffness, 24-hour blood pressure (BP) profile, and central aortic pressure (CAP) in patients with hypertension (HTN) and anxiety-depressive disorders (ADDs) during andro- and menopausal periods.Material and methods. The study included 120 patients with uncontrolled hypertension in the andro- and menopausal periods, of which 60 patients with hypertension and ADDs (30 men and 30 women) with median age of 58 years (52-64 years), as well as the control group — 60 patients with hypertension without ADD (30 men and 30 women) with median age of 59 years (53-65 years). All persons included in the study underwent 24-hour ambulatory BP monitoring (ABPM) and assessed the arterial stiffness parameters and CAP.Results. Comparative evaluation of ABPM in the group of patients with HTN and ADDs revealed more pronounced pathological changes in the 24-hour BP profile compared to those in the control group. Andro- and menopause with a combination of HTN and ADDs characterized by significantly higher ABPM parameters than HTN without ADDs (regardless of the sex). At the same time, in the group of men with HTN and ADD in andropause, unfavorable changes in the main arterial stiffness parameters and CAP were more significant than in women with HTN and ADD during menopause (p<0,05). In the control men groups, in comparison with women, more pronounced unfavo-rable changes in certain vascular stiffness indicators, CAP and ABPM were recorded.Conclusion. In men and women in periods of andro- and menopause with HTN and ADDs, the features of arterial stiffness, CAP, and 24-hour blood pressure profile were verified in comparison with patients with HTN without ADDs. At the same time, the severity of unfavorable changes in the studied parameters in men with depression in andropause is more significant than in menopausal women.